Long‐Term Degradation of Passivated Emitter and Rear Contact Silicon Solar Cell under Light and Heat. Issue 1 (23rd November 2021) - Xiao, Chuanxiao; Johnston, Steve; Jiang, Chun-Sheng; LaSalvia, Vincenzo; Sulas-Kern, Dana B.; Kempe, Michael D.; Young, David L.; Jordan, Dirk C.; Al-Jassim, Mowafak M.; Repins, Ingrid
Abstract : Advanced designs enable high‐efficiency solar cells; however, more complex structures create new long‐term stability concerns. Herein, the long‐term degradation processes affecting advanced silicon solar cells using laboratory‐based illumination and heating over hundreds of hours are investigated. The activation energy for the degradation of voltage is estimated and the degradation rates to normal solar cell operating temperature ranges are extrapolated. The cell degradation observed at high temperatures in the lab is kinetically similar to the process affecting field‐deployed modules contributing to 0.37% year −1 of annualized degradation. Electroluminescence and photoluminescence mapping show that the degradation is dominated by minority carrier lifetime reduction. Suns−open‐circuit voltage and light beam‐induced current results indicate that the degradation could result from passivation degradation at the surface or defect formation in the near‐subsurface region, leading to increased minority carrier recombination. This work highlights a long‐term degradation process under elevated temperature and illumination that may continue to affect cells in an irreversible manner that is separate from recoverable light‐induced degradation and light‐ and elevated temperature‐induced degradation. Abstract : A long‐term degradation in modern silicon solar cells induced by light and heat is reported. By estimating activation energy, a degradation rate is extrapolated to be 0.37% year −1, consistent with the long‐term degradation rate predicted to be observed widely in field operation. The degradation is related to minority carrier lifetime decrease due to recombination at or near the front surface.